Family caregivers of chronically ill people: a bibliographic study - Sonia Silva Marcon; Mislaine Casagrande Lopes; Claúdia Regina Marchiori Antunes; Jandira Fernandes; Maria Angelica Pagliarini Waidman (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This is a qualitative bibliographic research study which aimed to identify in literature aspects related to family caregiving of chronically ill people and verify the change in their families' routine. Some criteria were used to select the material and one of them was to register, in the data basis of Latin American and Literature and Health Sciences, Nursing data bank, CAPES and Public Health Virtual Library dissertations data bank, the information obtained. Thirteen works were analyzed from April to June, 2005. Results showed that the caregiving familiy's role can be considered as easy and difficult, being classified in two thematic categories: 1- changes in family routine; 2- changes in family relationship. Assistance to caregiving family of careceiver or of chronically ill people should be understood as part of their rehabilitation process. Assisting the family and their needs, listening to them, acknowledging their strong points and providing support should be taken as health professionals' permanent activities. Key words: family, family caregiving.